Strategi Pengawasan Siaran Televisi Lokal Oleh Komisi Penyiaran Daerah - Windarto Windarto; Eko Nuriyatman; Rustian Mushawirya (Wajah Hukum, 2020)
This scientific article discusses the strategy of monitoring local television broadcasts by the regional broadcasting commission of Jambi Province. The research method used is juridical empirical to be able to find answers about how the local television broadcast conditions in Jambi Province and the monitoring strategy carried out by the regional broadcasting commission. Based on the research results, data shows that there are many violations, especially during the implementation of regional head elections and there are 12 (twelve) violations that have been given a reprimand sanction, the violations that occur are evenly distributed in all programs both advertising, news and cinema. Television broadcast surveillance strategy by monitoring broadcasts and receiving reports from the public. The theory used in this scientific article is the theory of legal effectiveness which reviews the success in implementing the law, failure in implementation and the factors that influence it. Because in this case the success in implementing the law on this scientific article is obeyed by the broadcasting institutions that are subject to sanctions. As for local television located outside Jambi City, the strategy was to form volunteer supervisors located in each district / city where local television was available.